Pengaruh Agile Leadership terhadap Komitmen Kerja pada Guru - Surwiti Surwiti; Ahiruddin Ahiruddin (Journal of Leadership, Organization, Vision, and Administration, 2026)
This research examines the influence of agile leadership on teachers’ work motivation in senior high schools. The study is grounded in the increasing demands of educational transformation in the digital era, which require adaptive and responsive leadership to support teachers’ performance. A quantitative approach with a correlational design was employed, involving 150 teachers selected using quota sampling. Data were collected through Likert-scale questionnaires measuring agile leadership and work motivation. The analysis used simple linear regression. The results indicate that agile leadership has a positive and significant effect on teachers’ work motivation. These findings suggest that adaptive, flexible, and collaborative leadership can foster a supportive work environment and enhance teachers’ motivation. This research highlights the importance of implementing agile leadership in educational settings to strengthen teachers’ engagement and effectiveness in responding to ongoing changes.